2001
DOI: 10.1063/1.1389478
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of hydrogen and helium co-implanted single-crystal silicon during annealing

Abstract: H + was implanted into single-crystal silicon with a dose of 1×1016/cm2 and an energy of 30 KeV, and then He+ was implanted into the same sample with the same dose and an energy of 33 KeV. Both of the implantations were performed at room temperature. Subsequently, the samples were annealed in a temperature range from 200 to 450 °C for 1 h. Cross-sectional transmission electron microscopy, Rutherford backscattering spectrometry/channeling, elastic recoil detection, and high resolution x-ray diffraction were emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…In order to improve the robustness of the film against the etching solution, silicon nitride was deposited at a higher temperature of 250 • C, and to improve the fraction of open blisters, an inert gas plasma pretreatment prior to silicon nitride deposition is proposed. It was previously reported by Duo et al that by coimplanting helium and hydrogen into silicon, the smart cut process can be carried out more efficiently [28]. A reduction in implant dose, implant time, and lower crystal damage were reported as the benefits of helium-hydrogen coimplant [28].…”
Section: Impact Of Plasma Pretreatment On Blister Formationmentioning
confidence: 99%
“…In order to improve the robustness of the film against the etching solution, silicon nitride was deposited at a higher temperature of 250 • C, and to improve the fraction of open blisters, an inert gas plasma pretreatment prior to silicon nitride deposition is proposed. It was previously reported by Duo et al that by coimplanting helium and hydrogen into silicon, the smart cut process can be carried out more efficiently [28]. A reduction in implant dose, implant time, and lower crystal damage were reported as the benefits of helium-hydrogen coimplant [28].…”
Section: Impact Of Plasma Pretreatment On Blister Formationmentioning
confidence: 99%
“…He can induce a high pressure in the microcracks [3]. It has been reported that fluences of 1 Â 10 16 He + /cm 2 + 0.75 Â 10 16 H + /cm 2 can effectively induce layer splitting, while a fluence of 5 Â 10 16 H + /cm 2 is needed for H implantation alone [4]. Therefore, it greatly decreases the H fluence needed for layer splitting.…”
Section: Introductionmentioning
confidence: 97%
“…During short time annealing the total amount of helium did not change substantially until reaching temperature exceeding 720 K [1,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 98%